(untitled) (Encuentros, 2021)
This action research qualitative study unfolds the findings emerged on an online peer project targeting advanced English oral skills as well as collaboration and autonomy in a group of student-teachers at a Colombian University EFL programme. Data collection instruments included an online diagnosis, online weekly samples and feedback, follow-up surveys and final report. Findings revealed there was some significant development of oral skills in linguistic competence (pronunciation and lexicon), pragmatic competence, and fluency. Discursive and social competences improved as well. Collaborative work had a direct incidence over the progress learners made orally. Peer feedback facilitated metacognitive development: students gained awareness of own and peer´s mistakes, repaired them appropriately, and performed as feedback providers. Autonomous skills were connected to commitment, decision-making, and accountability.